(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Norovirus is The primary cause of acute conditions. gastroenteritis globally, particularly in children under five years old. This study aims to investigate the clinical epidemiology of norovirus infection among pediatric patients presenting with diarrhea at a regional public hospital. We conducted a retrospective analysis of children diagnosed with norovirus-induced diarrhea over a 12-month period, assessing demographic characteristics, clinical presentation, laboratory findings, and outcomes. Our findings indicate that norovirus is a significant etiological agent in pediatric diarrhea cases, underscoring the need for improved diagnostic and preventive strategies in healthcare settings.